Deconstructing Computer Poets: Making Selected Processes Available as Services. (15th June 2015) - Gervás, Pablo
Abstract : The article explores the potential of redefining as services a number of functionalities involved in poetry generation systems to better serve the challenge of working toward a yet unknown successful computational model of the creative task being addressed. This is performed by considering how some of the processes currently modeled in existing systems for poetry generation might be deconstructed into a set of services susceptible of being recombined in different ways to be integrated in other developments. Building on prior attempts to propose an evolutionary architecture that allows integration of a number of artificial intelligence technologies in combination, this article explores the advantages of service‐oriented architecture for reimplementing as publicly available services some selected functionality of the Wishful Automatic Spanish Poet (WASP) poetry generation system.